B2B buying decision-making and social media: examining the role of emotions and social media in organizational buying decisions - Syrovatka, Nathalie (2020)
Social media has increased in its usage and opportunities during the past decade and gained significance for B2B companies. The purchasing decision-making process can be shaped by using social media to trigger essential emotions of the buyers. However, the current literature landscape does not embody the same scope as it occurs in the economy. This study aims to understand the emotional states in the B2B buying decision-making process and the correlating impact of social media on buying behavior. A total of 12 in-depth semi-structured interviews were conducted and analyzed. The analysis reveals emotions such as expectation, joy, fear, excitement, interest, hope, and trust as the most commonly encountered ones in theB2B buying decision-making process. Further, it emphasizes the buyers' social media usage behavior and discloses social media as a tool to evoke emotions. The study contributes to an improved understanding of the emotional appeals and social media effect in the organizational purchasing decision. Hence, managerial implications consist, for instance, of an efficient resource allocation in terms of B2B social media campaigns.